Inflammatory Biomarkers Associated with Lethal Rift Valley Fever Encephalitis in the Lewis Rat Model - Caroline, Amy L.; Kujawa, Michael R.; Oury, Tim D.; Reed, Douglas S.; Hartman, Amy L. (Frontiers in Microbiology, 2016)
Rift Valley Fever (RVF) is an emerging viral disease that causes significant human and veterinary illness in Africa and the Arabian Peninsula. Encephalitis is one of the severe complications arising from RVF virus (RVFV) infection of people, and the pathogenesis of this form of RVF is completely unknown. We use a novel reproducible encephalitic disease model in rats to identify biomarkers of lethal infection. Lewis rats were infected with RVFV strain ZH501 by aerosol exposure, then sacrificed daily to determine the course of infection and evaluation of clinical, virological, and immunological parameters. Weight loss, fever, and clinical signs occurred during the last 1 – 2 days prior to death. Prior to onset of clinical indications of disease, rats displayed marked granulocytosis and thrombocytopenia. In addition, high levels of inflammatory chemokines (MCP-1, MCS-F, Gro/KC, RANTES, and IL-1β) were detected first in serum (3-5 dpi) followed by brain (5-7 dpi). The results of this study are consistent with clinical data from human RVF patients and validate Lewis rats as an appropriate small animal model for RVF encephalitis. The biomarkers we identified here will be useful in future studies evaluating the efficacy of novel vaccines and therapeutics.